Customer Satisfaction Analysis on Transactional Business in PT Trakindo Utama - Prasetya, Eka Budhi; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2012)
This study collected the customer’s voice that build the customer’s future expectation. The voice of the customers collected from transactional survey then analyzed with concurent triangulation method analyses. The result of the analysis generates several proposed solutions to become a benchmark to the existing business process and revaluation process conducted to improve the business performance. The improvements generated by revaluation process then increase the value proposition of Trakindo on the next transactional business. Findings in this research show that Trakindo’s value proposition is perceived high although several improvements needed to increase its value proposition. Customer’s voice shows that area of improvement in parts delivery and communication shall become the focus of immediate action. To improve its customer’s experience in doing business with Trakindo, Trakindo shall improve their current process. Several solutions were proposed in this study classified according to each area of improvement. To materialize the proposed solution, an implementation plan was proposed in this research. The implementation plan covered scope of work and deliverables and overall time line. The implementation plan is divided into two main categories, in which will be the continuous improvement on daily activities and the development of web based integrated customer support system. Keywords: customer’s experience, customer’s satisfaction, voice of customer, transactional business.